Effect of Flux Cored arc Welding Process Parameters on Corrosion Resistance of Austenitic Stainless Steel Claddings - Nunes,Marlon Muniz (2020)
Abstract Cladding process can be used to create corrosion resistant surfaces from low cost materials. Austenitic stainless steel has been extensively used for weld cladding. It has excellent corrosion resistance and good weldability. In this context, experiments were conducted by depositing AWS E316LT1-1/4 stainless steel on to AISI 1020 carbon steel and the effects of flux cored arc welding (FCAW) process parameters on pitting and intergranular corrosion was investigated. Response surface methodology (RSM) based central composite design (CDD) was used to predict and develop the mathematical models for process parameters on corrosion resistance. The responses of interest were obtained by double loop electrochemical potentiokinetic reactivation (DLEPR) and potentiodynamic polarization tests. The process parameters analyzed were the wire feed rate, welding voltage, welding speed and nozzle to plate distance. All RSM models developed were statistically significant and presented good adjustments. The results indicated that the process parameters are important in determining the degree of sensitization and pitting potential, and the interaction between parameters cannot be neglected.